Why does water accelerate organic reactions under heterogeneous condition? - Manna, Arpan; Kumar, Anil (Journal of Physical Chemistry A, 2013)
An exhaustive kinetic analysis has been carried out to offer the convincing evidence of the involvement of the oil water interface in guiding ``on water organic reaction'' mechanism. We have tuned the interface to prove its indispensable efficacy to make on water reaction a unique type among water mediated organic reactions. Sensitive techniques have established the preferential salvation of polarizable ions at the water surface. The experimental methods have been developed to control the molecular structure of oil water interface in situ. Temperature-dependent analyses have also been presented to understand the enthalpic and entropic modifications of the interfacial water molecules during a heterogeneous reaction. Both of our kinetic and thermodynamic outcomes have univocally established that the hydrogen-bonding ability of the surface water molecules plays a critical role in deciding the on water organic reaction mechanism. The results have important implications on understanding the role of small water molecules adjacent to the reactants during the reactions discussed in this investigation.